Attitudes of U.S. Purchasing Managers Toward Industrial Products Manufactured in Selected Western European Nations - White, Phillip D. (Journal of International Business Studies, 1979)
This study reports the findings of a research project which focused on the stereotypes that United States purchasing managers have about industrial products manufactured in England, France, Italy, and West Germany, as well as the United States. The objective of the research was to determine what stereotypes, if any, exist in the minds of industrial buyers as they consider industrial products from these Western European nations. The findings suggest that stereotypes do exist for industrial products being traded by these nations. Managerial implications for marketing managers are discussed.